Blockade of the AHR restricts a Treg-macrophage suppressive axis induced by L-Kynurenine - Luis Felipe Campesato (Nature Portfolio, 2020)
The tryptophan metabolite kynurenine is an endogenous ligand of the aryl hydrocarbon receptor (AHR). Here, the authors show that AHR targeting in IDO/TDO-expressing tumours counteracts a regulatory T cell/macrophage suppressive axis and synergizes with immune checkpoint blockade to hinder tumour growth.